Glycoprotein VI oligomerization in cell lines and platelets. - Berlanga, O; Bori-Sanz, T; James, JR; Frampton, J; Davis, S; Tomlinson, MG; Watson, S (2007)
BACKGROUND: Glycoprotein VI (GPVI) is a physiologic receptor for collagen expressed at the surface of platelets and megakaryocytes. Constitutive dimerization of GPVI has been proposed as being necessary for the interaction with collagen, although direct evidence of dimerization has not been reported in cell lines or platelets. OBJECTIVES: To investigate oligomerization of GPVI in transfected cell lines and in platelets under non-stimulated conditions. METHODS AND RESULTS: By using a combination of molecular and biochemical techniques, we demonstrate that GPVI association occurs at the surface of transfected 293T cells under basal conditions, through an interaction at the extracellular domain of the receptor. Bioluminescence resonance energy transfer was used to confirm oligomerization of GPVI under these conditions. A chemical crosslinker was used to detect constitutive oligomeric forms of GPVI at the surface of platelets, which contain the Fc receptor (FcR) gamma-chain. CONCLUSIONS: The present results directly demonstrate GPVI-FcR gamma-chain oligomerization at the surface of the platelet, and thereby add to the growing evidence that oligomerization of GPVI may be a prerequisite for binding of the receptor to collagen, and therefore for proper functioning of platelets upon vascular damage.